Analysis of The Potential of The Metaverse in The Education Sector in Indonesia - Muhammad Ikhsanuddin; Kholil; Muhtar Hidayat; Rizka Setiawan; Slamet Budiyono5 (UNIVERSITAS SERAMBI MEKKAH, 2024)
The Metaverse is an innovation in 3D virtual space technology, and its rapid development and implementation have sparked curiosity among many people and have been widely used in various fields. This research study explains the challenges and opportunities of the Metaverse in the field of education and its application in the educational world. The research method used is a literature survey by collecting data from various sources in academic journals relevant to the discussed topic. A narrative review will be used as the research design. Data collection is summarized from articles in international journals, accredited national journals, and proceedings, from the years 2017 to 2022. The research results show that the popularity of the Metaverse has peaked in recent months, and the acceleration of Metaverse technology in the education sector can be observed through the implementation of digital learning media based on augmented reality and virtual reality. The Metaverse is believed to overcome existing limitations in the educational world, such as classroom capacity restrictions due to the pandemic, and limitations of distance and time in attending classes, among others. The concept of a virtual world makes online learning more interactive without sacrificing the learning experience of students. Learning anytime, anywhere is an appealing concept embraced by many Gen Z individuals today. The Metaverse is expected to enter many areas of human life in the next 10-15 years.